2017
DOI: 10.3390/toxins9010042
|View full text |Cite
|
Sign up to set email alerts
|

Detoxification of Aflatoxin B1 by Zygosaccharomyces rouxii with Solid State Fermentation in Peanut Meal

Abstract: Aflatoxins are highly carcinogenic, teratogenetic, and morbigenous secondary metabolites of Aspergillus flavus and A. parasiticus that can contaminate multiple staple foods, such as peanut, maize, and tree nuts. In this study, Zygosaccharomyces rouxii was screened out and identified from fermented soy paste-one kind of traditional Chinese food-to detoxify aflatoxin B 1 (AFB 1 ) by aerobic solid state fermentation in peanut meal. The optimal degradation condition was chosen from single factor experiment, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 29 publications
0
19
0
1
Order By: Relevance
“…Being produced by the Aspergilli species including Aspergillus flavus , Aspergillus nomius , and Aspergillus parasiticus [3], aflatoxins cause an economical loss of $1.68 billion in the United States annually [4]. There are more than 20 types of aflatoxins including AFB 1 , AFB 2 , AFG 1 , and AFG 2 , among which AFB 1 is the most toxic, causing severe liver damage [5]. Zearalenone (ZEN), a mycotoxin with estrogenic potency [6] causing swelling of the vulva and infertility in swine [7], is instead produced by the Fusarium species, such as Fusarium graminearum and Fusarium culmorum [8].…”
Section: Introductionmentioning
confidence: 99%
“…Being produced by the Aspergilli species including Aspergillus flavus , Aspergillus nomius , and Aspergillus parasiticus [3], aflatoxins cause an economical loss of $1.68 billion in the United States annually [4]. There are more than 20 types of aflatoxins including AFB 1 , AFB 2 , AFG 1 , and AFG 2 , among which AFB 1 is the most toxic, causing severe liver damage [5]. Zearalenone (ZEN), a mycotoxin with estrogenic potency [6] causing swelling of the vulva and infertility in swine [7], is instead produced by the Fusarium species, such as Fusarium graminearum and Fusarium culmorum [8].…”
Section: Introductionmentioning
confidence: 99%
“…AFB 1 was analyzed according to retention time in HPLC system equipped with a ZORBAX Eclipse XDB-C18 column (4.6×150 mm, 5um, Agilent, Palo Alto, CA, USA) and a 470 fluorescent detector (G1321A, Agilent, USA) (λexc 360 nm; λem 440 nm) using a mobile phase solvent of 10% acetonitrile, 40% methanol, and 50% water. The flow rate was 0.8 ml min −1 and injection volume was 20 μl (25).…”
Section: Methodsmentioning
confidence: 99%
“…Zygosaccharomyces rouxii from fermented soy paste [138]. The authors demonstrated nonviable cell binding and biotransformation of AFB 1 in which reduction was monitored by LC/MS.…”
Section: Novel Approaches For Tackling Aflatoxin Contaminationmentioning
confidence: 99%